Thymine DNA glycosylase modulates DNA damage response and gene expression by base excision repair‐dependent and independent mechanisms. (20th March 2017) - Nakamura, Tomohumi; Murakami, Kouichi; Tada, Haruto; Uehara, Yoshihiko; Nogami, Jumpei; Maehara, Kazumitsu; Ohkawa, Yasuyuki; Saitoh, Hisato; Nishitani, Hideo; Ono, Tetsuya; Nishi, Ryotaro; Yokoi, Masayuki; et al.
Abstract : Thymine DNA glycosylase (TDG) is a base excision repair (BER) enzyme, which is implicated in correction of deamination‐induced DNA mismatches, the DNA demethylation process and regulation of gene expression. Because of these pivotal roles associated, it is crucial to elucidate how the TDG functions are appropriately regulated in vivo . Here, we present evidence that the TDG protein undergoes degradation upon various types of DNA damage, including ultraviolet light (UV). The UV‐induced degradation of TDG was dependent on proficiency in nucleotide excision repair and on CRL4 CDT 2 ‐mediated ubiquitination that requires a physical interaction between TDG and DNA polymerase clamp PCNA. Using the Tdg ‐deficient mouse embryonic fibroblasts, we found that ectopic expression of TDG compromised cellular survival after UV irradiation and repair of UV‐induced DNA lesions. These negative effects on cellular UV responses were alleviated by introducing mutations in TDG that impaired its BER function. The expression of TDG induced a large‐scale alteration in the gene expression profile independently of its DNA glycosylase activity, whereas a subset of genes was affected by the catalytic activity of TDG. Our results indicate the presence of BER‐dependent and BER‐independent functions of TDG, which are involved in regulation of cellular DNA damage responses and gene expression patterns.